Identifying distinct sets of predictors of specific functions of autobiographical memory. Issue 9 (21st October 2019) - Lind, Majse; Demiray, Burcu; Bluck, Susan
ABSTRACT: Grounded in the ecological approach, research has charted several adaptive functions of autobiographical remembering. Each represents a rather different psychosocial domain (i.e., self, social, directive). The goal of this research was to determine the contributions of each of a set of variables, controlling for all others, in predicting use of autobiographical memory to serve each specific function. In two studies, participants ( N  = 100; N  = 195) rated frequency of functional use of specific event memories and completed a brief battery of memory-related measures. Most Study One results were replicated in Study Two. Self-relevance of memories was related to their functional use regardless of domain. Each function was also, however, predicted by a unique set of variables consistent with its use in a given psychosocial domain. Findings emphasise how a combination of factors come into play to allow humans to use autobiographical memory to serve various different functions in navigating daily life.